STRATEGI PEMERINTAH DALAM PENGEMBANGAN HILIRISASI KOMODITAS NANAS BIKANG DI KECAMATAN TOBOALI: Local Government’s Strategy in Development of Bikang Pineapple Comodities in Toboali District - Purnama, Eriko; Evahelda, Evahelda; Agustina, Fournita (Program Studi Magister Ilmu Pertanian, Fakultas Pertanian, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2023)
the pineapple plant (Ananas comosus (L.). In South Bangka Regency, especially in Bikang Village, Toboali District, pineapple has great potential to be developed , there is still a lot of unused land in various locations which is an area that has the potential to develop pineapple.With abundant production of bikang pineapple and it can be developed by innovating processed products, then the economic potential of the bikang pineapple is increasingly promising. So based on this explanation the purpose of this research is to see how the government's strategy is to make Bikang Village a place for downstream development of Pineapple. The research was carried out in Bikang Village, Toboali District, South Bangka Regency with the selection of locations carried out using the purposive method of considering Bikang Village which is a pineapple production center as well as bikang pineapple which has been registered as a local genetic resource. This research is categorized in descriptive qualitative research by observing the stages that have been carried out by the local government. From the results of observations of the stages that have been carried out by the government in making Bikang Village a place for pineapple downstream development, it is concluded that the government has taken definite steps and evidence that the local government is serious about making Bikang Village a place for pineapple downstream development is that the stages that have been implemented have progressed more than 50% and will continue to increase until the level of implementation becomes 100%.